The Effect of Phospholipase C on Platelet Factor 3 in Human Blood Platelets - Otnaess, A-B; Prydz, H (Thrombosis and Haemostasis, 1977)
Intact human platelets isolated by gel filtration have been treated with purified phospholipase C. The effect of the enzyme on available and total platelet factor 3 has been tested.The available procoagulant platelet factor 3 was very low. A further small reduction was observed after incubation with phospholipase C when the enzyme was washed away before testing.External attack on platelets by phospholipase C led to a marked inactivation of total platelet factor 3.